A Current-Mode based Field-Programmable Analog Array for Signal Processing Applications - Embabi, S. H.K.; Quan, X.; Oki, N. [UNESP]; Manjrekar, A.; Sánchez-Sinencio, E. (Springer Nature, 1998)
This paper presents a new approach to develop Field Programmable Analog Arrays (FPAAs),1 which avoids excessive number of programming elements in the signal path, thus enhancing the performance. The paper also introduces a novel FPAA architecture, devoid of the conventional switching and connection modules. The proposed FPAA is based on simple current mode sub-circuits. An uncompounded methodology has been employed for the programming of the Configurable Analog Cell (CAC). Current mode approach has enabled the operation of the FPAA presented here, over almost three decades of frequency range. We have demonstrated the feasibility of the FPAA by implementing some signal processing functions.
Keywords: Continuous time filters; Current-made circuits; Field-programmable analog array